The Current State of Anomie in Angola - Blanes, Ruy Llera (Durkheimian Studies, 2019)
In this article I explore the contemporary relevance of Émile Durkheim's classic theory of anomie with respect to both the discipline of social anthropology and the study of politics in Africa. I take as a case study present-day, post-war Angola, where an activist mobilisation (the Revolutionary Movement) has engaged in what I call ‘anomic diagnostics’ in opposing the country's current regime. Through a political reading of Durkheim's theory, I suggest that, while the French author situates anomie and suicide as cause and consequence respectively within a conservative view of society, Angolan activists instead see anomie as the starting point for a progressive political proposition productive of rupture.